Description of a species of the genus Cheylostigmaeus willmann (Acari: Stigmaeidae) from Ekşisu Marsh, Turkey - Doğan, Salih; Dilkaraoğlu, Sibel; Fan, Qing-Hai; Sevsay, Sevgi; Erman, Orhan; Adil, Sezai (Systematic and Applied Acarology Society, 2015)
The discovery of both sexes of Cheylostigmaeus variatus sp. nov. from grassy soil at Ekşisu marsh in Turkey adds more data to our knowledge of this genus. We herein describe and illustrate it and also provide a key to the known species in Turkey. © Systematic & Applied Acarology Society.
Keywords: Acari; Ekşisu marsh; New species; Raphignathoidea; Taxonomy; Turkey